Breadfruit leaf extract: A potential hypolipidemic and antioxidant agent in diabetes - Tanjaya, Angela; Yunus, Muhammad; Nasution, Ali Napiah; Halim, Binarwan; Hutagalung, Mangatas HP; Sitanggang, Holan Dianju Melva Meinaria (Buletin Kedokteran & Kesehatan Prima, 2024)
Elevated total cholesterol levels are medically termed as hypercholesterolemia. Breadfruit leaves are recognized for their health benefits owing to the presence of secondary metabolites. This study aimed to investigate the effect of breadfruit leaf extract (Artocarpus altilis) on total cholesterol levels in white rats (Rattus norvegicus) and assess its antioxidant potential. Two control groups were established: negative control (1% Na-CMC) and positive control (simvastatin). The three treatment groups were administered different doses of the breadfruit leaf extract (100, 200, and 400 mg/kg body weight). Each group consisted of five rats. The results indicated that 400 mg/kg body weight of breadfruit leaf extract significantly reduced total cholesterol levels in rats by 29.27% (p<0.05). The antioxidant activity of breadfruit leaf extract was evaluated using the DPPH method at concentrations of 100, 200, 300, 400, and 500 μg/ml. The maximum wavelength used was 516 nm, and the absorbance was measured using a UV-Vis spectrophotometer. The linear regression equation obtained for breadfruit leaf extract was Y = 0.1171x + 35.76, with an IC50 value of 121.605 μg/ml, indicating moderate antioxidant activity. In contrast, the linear regression equation for vitamin C was Y = 0.6378x + 26.083, with an IC50 value of 37.499 μg/ml, indicating a very strong antioxidant activity.